2018
DOI: 10.3892/mmr.2018.8534
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl acetate extract from Inula�helenium L. inhibits the proliferation of pancreatic cancer cells by regulating the STAT3/AKT pathway

Abstract: Sesquiterpene lactones are bioactive compounds that have been identified as responsible for the anticancer activity of the medicinal herb, Inula helenium L. (IHL). However, the mechanisms of action involved in the anti‑pancreatic cancer activity of IHL have yet to be elucidated. The present study used an optimized extraction strategy to obtain sesquiterpene lactones from IHL (the resulting product termed ethyl acetate extract of IHL; EEIHL), and examined the potential mechanisms involved in the anti‑pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…alantolactone, isoalantolactone, 5αepoxyalantolactone, (iso) costunolide and igalan) in cancer therapeutics. Antineoplastic [38] and anti-cancer activity was demonstrated in multiple cell lines, including brain [39], pancreatic [40] and breast [41] cancers. Other studies reported reduced inflammatory responses in in vivo sepsis models [42,43], rheumatoid arthritis [44] and suppressed neutrophilmediated inflammation in acute bronchitis by down-regulating the β2-integrin [45], following exposure to the crude extract.…”
Section: Traditional Use To Modern Researchmentioning
confidence: 99%
“…alantolactone, isoalantolactone, 5αepoxyalantolactone, (iso) costunolide and igalan) in cancer therapeutics. Antineoplastic [38] and anti-cancer activity was demonstrated in multiple cell lines, including brain [39], pancreatic [40] and breast [41] cancers. Other studies reported reduced inflammatory responses in in vivo sepsis models [42,43], rheumatoid arthritis [44] and suppressed neutrophilmediated inflammation in acute bronchitis by down-regulating the β2-integrin [45], following exposure to the crude extract.…”
Section: Traditional Use To Modern Researchmentioning
confidence: 99%
“…Inula helenium L is a Chinese herbal medicine that has been traditionally used to treat intestinal tuberculosis. It has also been reported to possess anticancer properties ( Zhang et al, 2018 ). Among the bioactive ingredients isolated from Inula helenium L, IATL has been demonstrated to possess considerable biological activities, including anticancer properties ( Chun et al, 2018 ; Yan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al showed that low concentrations of the extract of inula helenium caused cfpac-1 cell cycle arrest, whereas high concentrations induced mitochondria-dependent apoptosis. In addition, ethyl acetate extract of inula helenium inhibited the phosphorylation of the signal transducer and activator of the transcription (stat)3/akt pathway [136].…”
Section: Inula Heleniummentioning
confidence: 99%